Research of On-line Detection System of End-face Run-out of Synchronizer Gear Set - Shen Kai; Liu Feifei; Meng Dejiao (Jixie chuandong)
An on-line detection instrument for synchronizer tooth sets is designed. The instrument can better complete the data acquisition,run-out error processing and display. The whole system is composed of mechanical parts and control parts: the mechanical part automatically completes the detection and stacking of the measured teeth,the control part is controlled by the PLC to the manipulator,the run-out detection and the data processing can be realized by industrial personal computer,and the run-out error is corrected. The results show that the accuracy of the gear set is ± 3 μm. The measuring instrument has high precision and fast speed,and can be applied to the on-line detection of the synchronizer tooth set,which provides a new detection method and idea.